2009
DOI: 10.1089/neu.2008.0506
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cervical Dorsal Root Ganglia Induced by Compression Injury and Decompression Procedure: A Novel Rat Model of Cervical Radiculoneuropathy

Abstract: Our study aimed to establish a model of compression injury of cervical dorsal root ganglia (DRG) in the rat and to investigate the pathological changes following compression injury and decompression procedures. Thirty rats were divided into three groups: control group receiving sham surgery, compression group undergoing surgery to place a micro-silica gel on C6 DRG, and decompression group with subsequent decompression procedure. The samples harvested from the different groups were examined with light microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It is thus possible that mechanical stresses activate neuronal TRPV1 channels via the PLA 2 -12-HPETE pathway to induce the mechanical hypersensitivity of afferent nerves. Consistent with this idea, recent studies reported that the expression level of PLA 2 in DRG neurons was significantly elevated following compression injury or inflammation [51], [52]. Whether this pathway would contribute to the development of DMA in vivo will be an intriguing topic of the future study.…”
Section: Discussionmentioning
confidence: 57%
“…It is thus possible that mechanical stresses activate neuronal TRPV1 channels via the PLA 2 -12-HPETE pathway to induce the mechanical hypersensitivity of afferent nerves. Consistent with this idea, recent studies reported that the expression level of PLA 2 in DRG neurons was significantly elevated following compression injury or inflammation [51], [52]. Whether this pathway would contribute to the development of DMA in vivo will be an intriguing topic of the future study.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical studies revealed that QSP can significantly improve mild-to-moderate NP and improve the quality of life of patients with mild-tomoderate NP, especially concerning physiological function, social function, emotional function, vitality, and other aspects. In a number of randomized, double-blind, placebocontrolled studies, improvements in dysfunction associated with mild-to-moderate NP were observed in both the QSP and placebo group, although the improvement was significantly better in the QSP group [5]. To study the mechanism of action of QSP, this study relied on the TCMSP and BATMAN-TCM platforms to study the active constituents e results of this study suggest that QSP most likely exerts its therapeutic effects on NP through interactions among MOL021, MOL001, PTGS2, and PTGS1, thereby laying a foundation for subsequent confirmatory studies.…”
Section: Discussionmentioning
confidence: 98%
“…Qi She Pill (QSP) has been approved by the China Food and Drug Administration (approval number: Z20090978), and it is widely available in China [5]. QSP is composed of six Chinese herbs, namely Caulis Sinomenii (CS, Qing Feng Teng), Calculus Bovis (BC, Niu Huang), Chuanxiong Rhizoma (CR, Chuan Xiong), Stephaniae Tetrandrae Radix (STR, Fang Ji), Hedysarum Multijugum Maxim (HMM, Huang Qi), and Moschus (MO, She Xiang).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the restoration of lumbar intervertebral foramen space improves mechanical hypersensitivity and that decompression of the DRG reduces compression-induced decreases of DRG neurons [ 41 ]. Thus, it is possible to expect that gradual attenuation of CCD-induced mechanical hypersensitivity is due to the recovery of damaged CCD neurons by the gradual widening of the intervertebral foramen over a period of time after injury.…”
Section: Discussionmentioning
confidence: 99%